Pengaruh Pengetahuan Keuangan dan Sikap Keuangan Terhadap Perilaku Manajemen Keuangan - Abdul Salam; Iyuth Ummu Amini (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of the study was to test the influence of financial knowledge and financial attitudes on financial management behavior in private employees domiciled in Unter Iwes District, Sumbawa Regency. Using quantitative methods with an associative approach. Using a purposive sampling technique with a hundred respondents. The primary data obtained through the distribution of the questionnaire were regressed through SPSS. The results of the study, showed that financial knowledge had a significant effect on financial management behavior, the tcount value of 2.242 was greater than the table of 1.984, the significant value of 0.027 was smaller than 0.05; Financial attitudes have a significant effect on financial management behavior, the tcount value of 5.692 is greater than the ttable 1.984, the significant value of 0.000 is smaller than 0.05; Financial knowledge and financial attitudes together affect financial management behavior, the value of the calculation of 33.920 is larger than the calculation value of 3.090, the significant value of 0.000 is litter than 0.05.